Applied engineering failure analysis : theory and practice - Qua, Hock-Chye. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
"This book fills the gap between the traditional failure analysis theory and the actual conducts of the failure cases. The book demonstrates the main methodologies that have evolved from the 1970s to date. Calculation of engineering cases and estimation of system stress and strength are demonstrated in the chapters. A wide range of actual cases span a wide array of engineering fields, including power systems, metallurgy, mining, structures, and machines"--
Includes bibliographical references and index.
Keywords: Failure analysis (Engineering); SCIENCE / Mechanics / General; TECHNOLOGY & ENGINEERING / Industrial Design / General; TECHNOLOGY & ENGINEERING / Material Science